PERANCANGAN MOTION GRAPHIC UNTUK KAMPANYE ALAT MUSIK TRADISIONAL DARI BAMBU DI JAWA BARAT - Rizkita, Cindy Amzal Dara (Anggada : Jurnal Desain dan Seni, 2020)
There is many cultures in Indonesia, one of which is a traditional musical instrument. But along with the progress and development of the times, and the era of globalization, many foreign cultures entered Indonesia. People are more interested in outside cultures. Even though there are many traditional musical instruments that are not yet known, one of them comes from West Java, namely Karinding and Celempung. Both instruments are made of the same basic material, bamboo. Therefore, the authors designed a motion graphic video about traditional musical instruments from bamboo in West Java, namely Karinding and Celempung as a medium that provides information to the public, especially children. With this video, children can find out about Karinding and Celempung, and with the hope that Karinding and Celempung will not be forgotten until they grow up and help preserve Indonesian culture.